Live sport during the COVID-19 crisis: fans as creative broadcasters - Majumdar, Boria; Naha, Souvik (Sport in society, 2020)
The hiatus in stadium spectatorship due to the COVID-19 pandemic presents us with a unique opportunity to rethink the way sport fans participate in the making of live events. Some sport leagues have resumed, with others to follow, but the stadium experience has profoundly changed as fans cannot gather in the galleries until the spread of coronavirus is arrested. How can sport broadcasters continue to engage fans and mitigate the problem of the empty stadium? We argue that creative harnessing of user-generated content and integration of online and offline fandom can help broadcasters present sport in a much more attractive manner during and after the pandemic.